2014
DOI: 10.1007/s11663-014-0187-8
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Study of Carbon Surfaces Interacting with High Carbon Ferromanganese Slag

Abstract: The interaction of carbon materials with molten slags occurs in many pyro-metallurgical processes. In the production of high carbon ferromanganese in submerged arc furnace, the carbothermic reduction of MnO-containing silicate slags yields the metal product. In order to study the interaction of carbon with MnO containing slags, sessile drop wettability technique is employed in this study to reduce MnO from a molten slag drop by carbon substrates. The interfacial area on the carbon substrate before and after re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…The activation energy for Assmang charges is calculated to be 230 kJ/mol, significantly lower than that of Comilog charges (470 kJ/mol). This may explain why Comilog charges have significantly higher reduction rates at high temperature, as the activation energy is the factor showing the temperature dependency [20,21]. Table 5 illustrates the reported calculated activation energies for MnO reduction by carbon (solid or dissolved) from different studies.…”
Section: Reduction Behaviour Of Assmang and Comilog Orementioning
confidence: 99%
“…The activation energy for Assmang charges is calculated to be 230 kJ/mol, significantly lower than that of Comilog charges (470 kJ/mol). This may explain why Comilog charges have significantly higher reduction rates at high temperature, as the activation energy is the factor showing the temperature dependency [20,21]. Table 5 illustrates the reported calculated activation energies for MnO reduction by carbon (solid or dissolved) from different studies.…”
Section: Reduction Behaviour Of Assmang and Comilog Orementioning
confidence: 99%
“…researchers [10][11][12][13][14][15][16][17][18] studied and calculated equilibrium phase chemistry in the Al 2 O 3 -MgO-SiO 2 -CaO-MnO slag system. The slag basicity was optimized by flux addition to obtain the higher manganese recovery and qualified metal with slag containing Al 2 O 3 content at a range of 7.5 to 16.0 wt %, and an Al 2 O 3 /SiO 2 weight ratio of 0.2-0.5.…”
Section: B (2019) 331 -342mentioning
confidence: 99%
“…The reported activation energy for the carbothermal reduction of MnO ranges from 332 to kJ/mol [7,8,28,29], and for the carbothermal reduction of SiO2, the range is 796-870 kJ/mol [22,25,30]. Therefore, the reduction of MnO and SiO2 is highly sensitive to temperature.…”
Section: Reduction Kineticsmentioning
confidence: 99%
“…In recent decades, the kinetics of MnO reduction in the field of ferromanganese (FeMn) production processes, where solid MnO still exists, have been studied extensively [5][6][7][8]. In this process, the activity of MnO is hence much higher than in SiMn slag [5][6][7][8]. It has been observed that stirring has no effect on the kinetics of MnO reduction, while the reduction rate is highly sensitive to temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation